Investigation of the relationship between demographic factors and ergonomic risks assessed by the HEMPA method with musculoskeletal disorders among nurses - Yousefi Seyf, Nader; Variani, Ali Safari; Varmazyar, Sakineh (Theoretical issues in ergonomics science, 2024)
This study investigated the relationship between demographic factors and ergonomic risks assessed by the HEMPA method with musculoskeletal disorders among hospital nurses. This descriptive-analytical and cross-sectional study was conducted on nurses (n = 46) working in hospital settings. Demographic and Body Map questionnaires and the HEMPA method collected data. Based on the body map questionnaires, low back pain (43.1%) was the most prevalent musculoskeletal disorder among nurses. In examining the relationship between demographic variables and the prevalence of disorders/severity of pain, between height with the neck pain prevalence (χ 2 =7.84, p < 0.05) gender with the right wrist prevalence and neck pain prevalence (r = 0.44, p < 0.05; r = 0.42, p < 0.05 respectively), and marital status with the neck pain prevalence (r = 0.70, p < 0.01) statistically significant relationship were observed. The lowest scores sub-items of the HEMPA method were for training (score = 0), environmental conditions (score = 0.15), transfer execution and postural analysis (score = 0.3), and work organization (score = 0.5) items. The total score of the HEMPA for a hospital was 12.3, which showed that nurses' risk of musculoskeletal disorders was at a medium level. The score of the HEMPA has a significant and negative correlation with musculoskeletal disorders (r=-0.08, p < 0.05). Also, the results indicated that one of the seven hospital wards (HEMPA score related to men's orthopedic = 15.28) obtained one-half of the maximum score of 30. With the corrective measures, including training courses on proper patient handling, improving environmental conditions, increasing the number of nurses, reducing night working shifts, employing the proper equipment, and using minor aids/devices, the total score of the HEMPA will be increased. As a result, the prevalence of musculoskeletal disorders will be reduced.